(untitled) (Intent Research Scientific Journal, 2023)
Our studies of the social portrait and clinical manifestations of newly diagnosed pulmonary tuberculosis in young people with DR MBT identified a number of features. It was found that in patients with DR MBT, there was statistically significantly more often no permanent job, there were bad habits, mainly in the form of a combination of alcohol abuse and smoking. In this group of patients, concomitant pathology of other organs and systems, complications of the underlying disease, and one or more extrapulmonary localizations of the tuberculous process were more often diagnosed. Thus, the identified features of the social portrait, clinical manifestations and course of newly diagnosed pulmonary tuberculosis in young people make it possible to suspect the presence of MBT drug resistance even before obtaining the results of sputum culture and determining drug sensitivity.